Recent developments in organic–inorganic hybrid metal phosphates and phosphites. Issue 29 (2nd July 2021) - Li, Ying; Li, Han-Ying; Chang, Kai-Chi; Lin, Hsiu-Mei; Wang, Chih-Min
Abstract : This frontier article highlights recent advances in synthesis and characterization of organic–inorganic hybrid metal phosphates and phosphites. The synthetic strategies and structural stabilities of hybrid composites blended with stable crystalline compounds are presented. Abstract : The design and synthesis of crystalline materials have been a subject of intensive research because of their interesting structures, physicochemical properties, and potential applications. However, the crystalline structure of organic–inorganic hybrid materials collapses to lose the structural features of the original networks and/or frameworks when exposed to different stimuli such as pH, vapor, water, high temperature, and organic solvents. This hampers further studies focusing on practical applications. Although several review articles provide reasonable pathways for the preparation of stable metal–organic frameworks (MOFs) and coordination polymers (CPs), the synthesis and design of stable materials containing organic species remain challenging. In this frontier article, we discuss the development of crystalline MOF, CP, metallophosphate, and metallophosphite materials, and provide a feasible approach for the formation of stable organic–inorganic hybrid compounds that combine MOFs (or CPs) and phosphate (or phosphite) building elements. In addition to their interesting structures, the synthetic strategies and structural stabilities of such hybrid composites are also presented.